2009
DOI: 10.1128/jb.00390-09
|View full text |Cite
|
Sign up to set email alerts
|

Hopanoids Are Not Essential for Growth of Streptomyces scabies 87-22

Abstract: Hopanoids are triterpenoic, pentacyclic compounds that are structurally similar to sterols, which are required for normal cell function in eukaryotes. Hopanoids are thought to be an important component of bacterial cell membranes because they control membrane fluidity and diminish passive diffusion of ions, and a few taxons modulate their hopanoid content in response to environmental stimuli. However, to our knowledge, mutational studies to assess the importance of hopanoids in bacterial physiology have never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
0
37
1
1
Order By: Relevance
“…One of the few studies utilizing a genetic approach to define the role of hopanoids in membrane structure-function reported that the loss of hopanoid production in Rhodopseudomonas palustris resulted in sensitivity to acidic and alkaline conditions, bile salts, and certain antibiotics (72). This increased sensitivity was not observed in similar experiments performed with Streptomyces scabies (62), demonstrating that hopanoid function varies depending on taxonomy, environment, and physiology.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…One of the few studies utilizing a genetic approach to define the role of hopanoids in membrane structure-function reported that the loss of hopanoid production in Rhodopseudomonas palustris resulted in sensitivity to acidic and alkaline conditions, bile salts, and certain antibiotics (72). This increased sensitivity was not observed in similar experiments performed with Streptomyces scabies (62), demonstrating that hopanoid function varies depending on taxonomy, environment, and physiology.…”
mentioning
confidence: 64%
“…From the sequenced genome of B. cenocepacia J2315, we identified several gene clusters encoding putative hopanoid biosynthesis and transport genes. To date, every bacterium whose genome contains hopanoid biosynthesis genes has been found to produce hopanoids (23,53,57,62,72). The key step in hopanoid biosynthesis is the conversion of linear squalene to the basic hopene structure, which is catalyzed by squalene-hopene cyclase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the physiological role of sterols in eukaryotic membranes, BHPs appear to be involved primarily in membrane stabilization and were recently shown to have the same membrane-ordering properties as sterols (7). Unlike sterols in eukaryotic organisms, BHPs do not appear to be essential for overall cell growth and survival in bacteria (8,9), presumably because those that lack BHPs produce other membrane lipids to compensate. BHPs are also important in other membrane functions such as pH tolerance and antibiotic resistance (8,10), lipid raft formation (11), and late stationary-phase survival (12).…”
mentioning
confidence: 99%
“…It has recently been shown that hopanoids are not essential for the growth of some hopanoid producing bacteria (Welander et al, 2009;Seipke and Loria, 2009), which suggests that the biological role of hopanoids is not essential for survival. But, it is also possible that although hopanoids may not be essential in euxinic cultures under conditions selected for optimal growth, that they might serve a function that is crucial for survival in the environment.…”
Section: Resultsmentioning
confidence: 99%